2019
DOI: 10.1128/jvi.00699-19
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Thrips Vector Proteins That Bind to the Viral Attachment Protein of the Plant Bunyavirus Tomato Spotted Wilt Virus

Abstract: The plant-pathogenic virus tomato spotted wilt virus (TSWV) encodes a structural glycoprotein (GN) that, like with other bunyavirus/vector interactions, serves a role in viral attachment and possibly in entry into arthropod vector host cells. It is well documented that Frankliniella occidentalis is one of nine competent thrips vectors of TSWV transmission to plant hosts. However, the insect molecules that interact with viral proteins, such as GN, during infection and dissemination in thrips vector tissues are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 74 publications
(78 reference statements)
0
52
0
Order By: Relevance
“…In total, 96 innate immune genes were curated from the genome (Additional file 2: Table S17) [38,39,129,197,[212][213][214][215][216][217][218][219][220][221][222][223]. Toll and JAK-STAT pathway members were well represented, and all but two members of the IMD pathway were located.…”
Section: Innate Immunity Canonical Signaling Pathwaysmentioning
confidence: 99%
“…In total, 96 innate immune genes were curated from the genome (Additional file 2: Table S17) [38,39,129,197,[212][213][214][215][216][217][218][219][220][221][222][223]. Toll and JAK-STAT pathway members were well represented, and all but two members of the IMD pathway were located.…”
Section: Innate Immunity Canonical Signaling Pathwaysmentioning
confidence: 99%
“…Distribution of nucleotide variation and nucleotide diversity along segment M showed that variation mainly maps to the intergenic region ( Figure 6 B), with variation higher than average also detected at the C-terminal of NSm, at the ends of the glycoprotein and near the protease cleavage site in the glycoprotein ( Figure 6 B). Glycoprotein variation might be related to its interaction with thrips vectors [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…occidentalis , and T . tabaci [ 15 , 27 , 28 , 40 ]. The dissemination dynamics of TSWV is very similar in these three thrips species.…”
Section: Discussionmentioning
confidence: 99%